Prevalence and Visual Risk Factors for Falls in Bilateral Cataract Patients in Ho Chi Minh City, Vietnam - To, K.; Meuleners, Lynn; Fraser, Michelle; Do, D.; Duong, D.; Huynh, V.; To, Q.; Phi, T.; Tran, H.; Nguyen, N. (Informa Healthcare, 2014)
Purpose: To determine the prevalence of falls in the 12 months prior to cataract surgery and examine the associations between visual and other risk factors and falls among older bilateral cataract patients in Vietnam. Methods: Data collected from 413 patients in the week before scheduled cataract surgery included a questionnaire and three objective visual tests. Results: The outcome of interest was self-reported falls in the previous 12 months. A total of 13% (n = 53) of bilateral cataract patients reported 60 falls within the previous 12 months. After adjusting for age, sex, race, employment status, comorbidities, medication usage, refractive management, living status and the three objective visual tests in the worse eye, women (odds ratio, OR, 4.64, 95% confidence interval, CI, 1.85–11.66), and those who lived alone (OR 4.51, 95% CI 1.44–14.14) were at increased risk of a fall. Those who reported a comorbidity were at decreased risk of a fall (OR 0.43, 95% CI 0.19–0.95). Contrast sensitivity (OR 0.31, 95% CI 0.10–0.95) was the only significant visual test associated with a fall. These results were similar for the better eye, except the presence of a comorbidity was not significant (OR 0.45, 95% CI 0.20–1.02). Again, contrast sensitivity was the only significant visual factor associated with a fall (OR 0.15, 95% CI 0.04–0.53). Conclusion: Bilateral cataract patients in Vietnam are potentially at high risk of falls and in need of falls prevention interventions. It may also be important for ophthalmologists and health professionals to consider contrast sensitivity measures when prioritizing cataract patients for surgery and assessing their risk of falls.